OP18 Maternal alcohol use during pregnancy and offspring trajectories of height and weight: a prospective cohort. (2nd September 2014) - O'Keeffe, LM; Kearney, PM; Greene, RA; Zuccolo, L; Tilling, K; Lawlor, DA; Howe, LD
Abstract : Background: The National Institute for Health and Care Excellence [NICE] advise an upper limit of 1–2 units of alcohol not more than once or twice per week during pregnancy whereas guidelines elsewhere advocate complete abstinence. However, studies on the impact of alcohol intake during pregnancy on postnatal growth during childhood are sparse. The aim of this study was to examine the association between maternal alcohol consumption during pregnancy and offspring height and weight from birth to 10 years. Methods: We examined the association between maternal drinking during pregnancy and trajectories of offspring weight and height from 0–10 years in 7597 mother-child pairs in the Avon Longitudinal Study of Parents and Children (ALSPAC) using multilevel linear spline models in MLwin. Pregnant women resident in one of the three Bristol-based health districts with an expected delivery date between April 1991 and December 1992 were invited to participate in the study. Postal questionnaires at 18 weeks gestation collected information on the mother's and partner's alcohol consumption during the first trimester. Childhood growth data was collected through routine child health records and research clinics up to age 10 years. Models were adjusted for maternal education, parity, maternal smoking, maternal age, maternal height, maternal BMI and partner drinking. To strengthen the inference, we compared maternal drinking with partner drinking, to partially control for unmeasured confounding. We performed sensitivity analyses restricting to women of white ethnicity, participants with three or more growth measures and participants lost to follow-up after birth or excluded due to missing confounder data. Results: Maternal occasional or light daily drinking during pregnancy was not associated with reduced birth weight, birth length or offspring growth trajectories up to age 10 years. The infants of heavy drinking mothers were born 0.78 cm shorter (95% CI -1.34, -0.22) and 0.22 kg lighter (95% CI -0.34, -0.09) than infants of pregnancy abstainers but by age 10 offspring of heavy drinking mothers were of comparable height (mean difference 0.59 cm, 95% CI -0.93, 2.11) and weight (mean difference 0.41 kg, 95% CI -0.70, 1.52). These associations were not observed for heavy partner drinking and robust to sensitivity analyses restricting to women of white ethnicity, children with three or more growth measures and participants lost to follow-up after birth or excluded due to missing confounder data. Discussion: Maternal occasional or light daily drinking is not associated with birth weight, birth length or postnatal growth. Maternal heavy drinking may have an intrauterine association with reduced birth weight and length that is overcome during childhood. However, as residual confounding cannot be discounted policies advising abstinence from alcohol during pregnancy are the most prudent approach until further research becomes available.